A CASE OF A RARE CONGENITAL DEFECT OF THE MUSCULOSKELETAL SYSTEM - SIRENOMELIA IN COMBINATION WITH MEGACYSTIS AND A SINGLE UMBILICAL ARTERY - Наталия Игоревна Андрюк; Ольга Аркадьевна Соловьева; Светлана Леонидовна Стопичева; Людмила Викторовна Абрамова; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес (The Publishing House Medicine and Enlightenment, 2023)
Sirenomelia (mermaid syndrome) is a congenital pathology that occurs due to a violation of the blood supply to the embryo. It is characterized by fusion of the lower extremities in combination with agenesis of the kidneys, aplasia of the sacrum, rectum and bladder. The frequency of occurrence is 1 per 60 thousand newborns, the sex ratio is male / female 2.7 : 1. Sirenomelia does not belong to an inherited anomaly, most cases are sporadic, so the risk of relapse is not significant. This publication is devoted to the early diagnosis of a congenital malformation of the musculoskeletal system - sirenomelia in combination with megacystis and a single umbilical artery.